The Teacher in Technology-Based Learning Models: From Facilitator to Innovator - Safitri, Rani; Adillah, Suci; Andikos, Adi Fitra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Technological developments have brought significant transformation in the world of education, including the role of teachers in the learning process. This research aims to explore changes in the role of teachers from mere facilitators to innovators in technology-based learning models. Using a qualitative approach, data was collected through in-depth interviews, classroom observations, and document analysis on 10 teachers from various levels of education in the research area. The research results show that teachers who adopt technology-based learning are able to create an interactive and personalized learning atmosphere. As facilitators, teachers utilize technology to support information access and increase student involvement in learning. Meanwhile, in their role as innovators, teachers develop digital learning media, utilize online platforms, and design learning strategies that suit students' needs in the digital era. However, the challenges faced include limited infrastructure, lack of technology training, and resistance to change. This research recommends increasing support from educational institutions in providing technological facilities and ongoing training for teachers. In this way, teachers can continue to adapt and innovate in technology-based learning models, ensuring relevant and meaningful learning for students.